Multiepoch Observations of the Nearby Spiral Galaxy NGC 3938 with the Chandra X-Ray Observatory - Siddhi Raut; Eric M. Schlegel; Thomas G. Pannuti; Brannon W. Jones; Jacobo Matallana (The Astronomical Journal)
We present an analysis of two epochs of ACIS observations of the SA(s)c spiral galaxy NGC 3938 with the Chandra X-ray Observatory. The total exposure time of the observations was 95 ks, with a limiting unabsorbed luminosity of ≈10 ^38 erg s ^−1 assuming a distance of 22 Mpc. A total of 47 discrete merged sources from both epochs were detected at the ≈3 σ level or greater with the D25 radius. We demonstrate that at the time of the Chandra observations the nucleus was not detected. We connect the detected sources to counterparts in other wavebands to the degree possible. Based on the two epochs, we identify three variable sources and an additional two that may have varied between the two observations. We do not formally detect any of the five historical supernovae that have occurred in NGC 3938. The luminosity function of NGC 3938 is compared to a recent compilation of 38 galaxies, and we identify a potentially significant problem with the “known” distance to NGC 3938. Star formation rate and metallicity values are also computed; the star formation rate is highly dependent on the adopted distance. The metallicity appears to lie in the range of 8.2–9.2, consistent with values from other work. We include in an appendix a short discussion of the sources that lie in Chandra’s field of view but lie outside of NGC 3938.